Formes, acteurs et enjeux de la participation dans la genèse du Parc national des Cévennes (1950-1970) - Karine-Larissa Basset (Revue de Géographie Alpine)
The successive paradigms of French sociology have constructed a representation of the evolution of environmental participation that tends to contrast the so-called current « eco-citizen » phase, with a 1950-1970 phase which supposedly witnessed both a massive public adhesion to modernisation trends, and an authoritarian management by the State of diverging views. The recent reform of the French legislation on National parks is highly representative of this evolution. However, we here propose to revisit the 1950-1970 period, when most National parks were created, by focussing on the long and complex history of the “invention” of the Cévennes National Park. It actually appears that the Cévennes experience was characterised by a heavy involvement of local stakeholders, which may help moderate our sometimes too rigid perception of the evolution of participation levels. Moreover, the specificities of this participatory dynamics - and especially the importance of key individuals and interpersonal relations - should encourage us to better integrate in our analysis of governance matters some subjective aspects, as well as the interpretative capacity of the stakeholders.